Kewirausahaan Petani Kabupaten Bone: Sebuah Kolaborasi International Fund for Agricultural Development (IFAD) dan Indonesia - Aulia, Alifah Safira (Kolaborasi Masyarakat, 2025)
This study aims to analyze the impact of the Youth Entrepreneurship and Employment Support Services (YESS) Program on the development of youth entrepreneurship among young farmers in Bone Regency, as well as its contribution to increasing income and economic self-reliance in rural areas. The YESS Program is a collaborative initiative between IFAD and the Government of Indonesia through the Ministry of Agriculture, designed to address poverty, malnutrition, and low food productivity in rural regions through training, certified internships, competitive grants, and the Youth Agricultural Entrepreneurship Program (PWMP). This research employs a descriptive qualitative approach with field research methods, including direct data collection through observation, interviews, and documentation. The study is grounded in the theory of international cooperation, which explains how global collaboration can enhance local capacity. The findings indicate that the YESS Program has successfully promoted positive changes in entrepreneurial attitudes and skills among the younger generation in agriculture, created local business opportunities, and improved access to resources and markets. These findings affirm that international cooperation programs like YESS can be an effective strategy for supporting youth regeneration in farming and fostering sustainable rural development based on agribusiness.